2017
DOI: 10.1002/aic.15880
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of the BET area for nanoporous materials

Abstract: The Brunauer-Emmett-Teller (BET) method has been used extensively to characterize the surface areas of porous materials by semiempirical fitting of gas-adsorption isotherms. However, questions often arise concerning the applicability and the exact meaning of the BET areas. In particular, there has been much debate about whether the BET method provides a faithful description of the geometrical areas of porous materials if the atomic structures are exactly known. In this work, we provide a comprehensive analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 44 publications
4
42
0
Order By: Relevance
“…While NOSPC-2-900 displays mixed absorption curves of type I and type IV, implying the coexistence of micropores and mesopores. [13] Above results are further supported by the pore size distributions of these samples (see Figure 2b-…”
Section: Full Papersupporting
confidence: 63%
See 1 more Smart Citation
“…While NOSPC-2-900 displays mixed absorption curves of type I and type IV, implying the coexistence of micropores and mesopores. [13] Above results are further supported by the pore size distributions of these samples (see Figure 2b-…”
Section: Full Papersupporting
confidence: 63%
“…NOSPC‐2‐800 shows type I isotherm, indicating a predominant microporosity of the structure. While NOSPC‐2‐900 displays mixed absorption curves of type I and type IV, implying the coexistence of micropores and mesopores . Above results are further supported by the pore size distributions of these samples (see Figure b–d), highlighting the presence of micropores and mesopores with a portion of macropores favorable for rapid mass transport in the NOSPC‐1 materials.…”
Section: Resultsmentioning
confidence: 99%
“…However, in such instances every effort should be made to minimize the extent of deviation or use reasonable tolerances as suggested by Rouquerol et al for the 4th aspect of the criteria (20% tolerance). vii)Defects in experimentally synthesized samples have often been associated with differences when comparing the experimentally determined BET and the accessible surface areas. However, this review has demonstrated that deviations can also come from incorrectly determining the pressure ranges on adsorption isotherms. viii)A computational study by Tian and Wu discovered that the BET surface areas are very sensitive to the characteristics of MOFs such as pore size, structure heterogeneity, and adsorbate–adsorbent interactions. Therefore, they indicated that the accessible surface areas are not correlated to the BET surface areas despite their good agreements in particular studies. ix)The deviations between the accessible surface areas based on CO 2 and the BET surface areas obtained from simulated CO 2 adsorption isotherms at 273 K for different types of MOFs were higher than for the same materials when N 2 or Ar gas was employed.…”
Section: Discussionmentioning
confidence: 99%
“…However, this review has demonstrated that deviations can also come from incorrectly determining the pressure ranges on adsorption isotherms. viii) A computational study by Tian and Wu [59] discovered that the BET surface areas are very sensitive to the characteristics of MOFs such as pore size, structure heterogeneity, and adsorbate-adsorbent interactions. Therefore, they indicated that the accessible surface areas are not correlated to the BET surface areas despite their good agreements in particular studies.…”
Section: Figure 21mentioning
confidence: 99%
See 1 more Smart Citation